A novel broad-spectrum lytic phage vB_EcoM_P3322: isolation, characterization, and therapeutic potential against avian pathogenic Escherichia coli - Huang, Ying; Zhang, Mengfei; Tian, Yuan; Lan, Xueqin; Jin, Wanjing; Bai, Yixin; Zang, Qirui; Chen, Mingshuai; Su, Zhanqiang; Zhang, Wei; Aishan, Gulina; Geng, Mingyang; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe widespread misuse of antibiotics has accelerated the emergence of multidrug-resistant bacterial strains, presenting a major threat to global public health. Bacteriophages (phages), owing to their host-specific lytic activity and self-replicating nature, have emerged as promising alternatives or adjuncts to conventional antibiotic therapies.MethodsIn this study, a lytic phage targeting avian pathogenic Escherichia coli (APEC) was isolated from farm wastewater. The phage’s morphological characteristics, host range, optimal multiplicity of infection (MOI), one-step growth curve, pH stability, thermal stability, chloroform sensitivity, and in vitro antibacterial activity were determined. Subsequently, the therapeutic efficacy of the phage was evaluated in a pigeon model.ResultsIn this study, we isolated and characterized a lytic phage, designated vB_EcoM_P3322, from farm wastewater targeting APEC. Transmission electron microscopy classified vB_EcoM_P3322 within the Myoviridae family. The phage exhibited broad lytic activity against five Escherichia coliserotypes (O8:H10, O15:H18, O51:H20, O149:H20, and O166:H6). Optimal biological parameters included a multiplicity of infection (MOI) of 1, a latent period of 10 minutes, an 80-minute burst period, and a burst size of 252 PFUs/cell. vB_EcoM_P3322 maintained stable lytic activity across a pH range of 5–9 and temperatures from 4°C to 50°C, although it was sensitive to chloroform. In vitro, the phage effectively suppressed bacterial growth within 6 hours at MOIs of 0.1, 1, and 10. Whole-genome sequencing revealed a 151,674 bp double-stranded DNA genome encoding 279 predicted open reading frames. No virulence factors, toxin genes, antibiotic resistance genes, or lysogeny-related elements were identified, affirming its safety for therapeutic application. Phylogenetic analysis indicated 98.44% nucleotide identity (97% coverage) with phage vB_EcoM_Ro121c4YLVW (GenBank: NC_052654), suggesting a close evolutionary relationship. In a pigeon infection model, vB_EcoM_P3322 treatment significantly improved survival and reduced histopathological damage in the liver and spleen. Metagenomic analysis of duodenal contents revealed a marked reduction (P < 0.01) in E. coli abundance in the treatment group, indicating selective pathogen clearance and modulation of gut microbiota.DiscussionIn summary, vB_EcoM_P3322 displays broad-spectrum lytic activity, robust environmental stability, potent antibacterial efficacy both in vitro and in vivo, and a safe genomic profile. These attributes support its potential as a novel biocontrol agent for managing APEC infections in poultry farming.